“God in Himself” and “God as revealed to us”: the impact of the substance concept - Strauss, D. F. M. (Faculty of Theology, University of the Free State, 2010)
The static space metaphysics of the Eleatic school (Parmenides) is continued by Plato, Aristotle and subsequently followed up by Thomas Aquinas. Concurrently a negative theological approach surfaced, claiming that one can only say what God is not. It runs from Plato’s dialogue Parmenides and is continued via the Cappadocians, Plotinus, Pseudo-Dionysius and certain elements in the thought of Augustine and Thomas Aquinas. What is constant is elevated into the unknowable essence of God. There are two options. The first option (theo-ontologically) duplicates (accommodates) the creational diversity into the communicable (appearance) part of God — as the counter-pole of the esse(nce) part (namely “God-in-Himself”). In the second option, still as the counter-pole of the esse(nce) part (namely “God-in-Himself”), God accommodated Himself to the creational diversity in order to explain the “appearance” (revelation) of God to creatures. The distinction between conceptual knowledge and concept-transcending knowledge provides an alternative approach.
Keywords: Substance; Negative theology; Theo-ontology; Conceptual knowledge; Concept-transcending knowledge